On the Usage of Tapered Undulators in the Measurement of Interference in the Intensity-Dependent Electron Mass Shift - Maksim A. Valialshchikov; Marcel Ruijter; Sergey G. Rykovanov (Crystals, 2021)
In nonlinear Thomson scattering, the main emission line and its harmonics form a band-like structure due to the laser pulse shape induced ponderomotive broadening. We propose to use tapered undulators to mimic Thomson scattering and measure the intensity-dependent electron mass shift experimentally. We also numerically show that the effect is observable for realistic electron beams like in DESY or SKIF.